Management of non-muscle-invasive and muscle-invasive bladder cancers - (:unkn) unknown (Springer International Publishing, 2017)
Bladder cancer (BC) is the 7th most commonly diagnosed cancer in men worldwide, while it declines to 11th when both sexes are considered. The worldwide age-standardized incidence rate (per 100,000 person/years) is 9.0 for men and 2.2 for women. Europe has among the highest incidence rates of BC in the world, where the age-standardized incidence rate is 19.1 for men and 4.0 for women. The overall burden was greater in men; however varying incidence trends by gender were reported recently in some countries, with rates drop in male and increase in female population. The management of BC should be tailored according to the disease stage, grade, and patient-related factors at the presentation. In this chapter, we will discuss the management of non-muscle- invasive disease and the surgical management of muscle-invasive disease. © Springer International Publishing AG 2017.